Rantai nilai dan perspektif kesadaran masyarakat muslim akan makanan halal - Pratiwi Subianto (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
For Muslim consumers, halal food is a product with halal certification marked by a halal symbol on the packaging. The development of halal food and beverages continues to increase along with the growth of the Muslim population. This study aims to collect and analyze journals related to the value chain and the public awareness perspective on halal food. The research method is qualitative. The results of the study that public awareness of the importance of consuming halal food and beverages can encourage Halal Value Chain (HVC). Suggestions for in-depth research are related to the driving factors and inhibitors of halal value chains in the regions.For Muslim consumers, halal food is a product with halal certification marked by a halal symbol on the packaging. The development of halal food and beverages continues to increase along with the growth of the Muslim population. This study aims to collect and analyze journals related to the value chain and the public awareness perspective on halal food. The research method is qualitative. The results of the study that public awareness of the importance of consuming halal food and beverages can encourage Halal Value Chain (HVC). Suggestions for in-depth research are related to the driving factors and inhibitors of halal value chains in the regions.